A novel anatomy-based five-points eight-line-segments technique for precision subtotal tongue reconstruction: A pilot study. (February 2019) - Fan, Song; Zhang, Hanqing; Li, Qunxing; Liang, Faya; Bai, Zhiqiang; Chen, Weixiong; Sun, Sheng; Yu, Peirong; Li, Jinsong
Highlights: FIPELS flap was arisen from virtual dissection of the subtotal tongue. FIPELS technique could provide a natural-shape subtotal tongue contour. Functional and cosmetic outcomes are significantly improved by FIPELS technique. Abstract: Objectives: A no-flap design based on actual tongue anatomy has been reported to achieve precise reconstruction, but large carcinologic tongue defects remain extremely challenging to treat. The aim of this pilot study was to explore an anatomy-based flap design for precision subtotal tongue reconstruction. Material and methods: Thirty-five patients were randomly divided into two groups, a "five-points eight-line-segments" (FIPELS) technique flap design group (18 patients) and a conventional surgery group (17 patients), to undergo subtotal tongue reconstruction. All patients received an anterolateral thigh flap with nerve coaptation to the lingual or glossopharyngeal nerve. Swallowing function, speech intelligibility, and cosmetic results were assessed with a Likert scale, and epicritic and proprioceptive sensitivity and thermosensation of the neotongue were investigated. Outcomes were analyzed, and a p-value < 0.05 was considered significant. Results: The FIPELS flaps were significantly larger than conventionally designed flaps. All flaps healed uneventfully, except in two patients who presented with partial necrosis. Relative to patients in the conventional group, patients in the FIPELS group showed significantly improved swallowing function (p = 0.043) and cosmetic results (p = 0.017) but not speech intelligibility (p = 0.154). Patients in the two groups recovered comparably in terms of epicritic and proprioceptive sensitivity and thermosensation. Conclusion: The anatomy-based FIPELS technique is an innovative and effective solution for subtotal tongue reconstruction.